Legal certainty through clarity and easy access to the law - راضي مازن ليلو (Journal of Legal Sciences, 2019)
The basis of legal clarity is contrary to the idea of natural justice, it is fair and fair that the law is clear and easy to understand, and this principle is today one of the most important elements of legal certainty through which the legislation is sought and the individuals are assured of their rights and subject to the obligations incumbent upon them , Clarity is achieved by paying attention to the issue of legal drafting and assigning it to specialists, with the aim of achieving the application of the rule of law and good governance and enacting well-developed and sophisticated legislation, in harmony with the Constitution and not in contradiction with other laws , and a concept in the general public and workable.